Splendours of the vijayanagara empire Hampi - Michell, George [ed.]; Filliozat, Vasundhara [ed.] (Bombay Marg Publications, 1981)
One of the greatest UNESCO heritage sites in India, the ruins at Hampi are the remains of a medieval kingdom$1 (Bthe magnificent Vijayanagar. On the longlist of the Vodafone Crossword Book Award 2010, this book brings to surface the lost glory of this city.s
Keywords: India -- Hampi -- Hindu temples; Asia--Vijayanagar (Empire) -- Architecture -- Civilization